Fish Landing Base in Pantai Cermin with Ecological Architecture Approach - Daffa Farras Arfy; Imam Faisal Pane (Talenta Publisher, 2022)
Indonesia is a maritime country that has a sea area of ​​5.8 million km², with enormous potential for marine products. The fisheries sector is one of the things that supports the third largest Indonesian economy with a GDP (Gross Domestic Product) of Rp 1.900 billion. There are many fishery ports in Indonesia commonly referred to as Fish Landing Base. In North Sumatra itself, there are 23 Fish Landing Base, and one of the areas that include it in the RTRW (Regional Spatial Plan) is Serdang Bedagai Regency, especially in Cermin Beach sub-district. However, the fact that the fisheries sector is not the main attraction of the Pantai Cermin area indicates no fishery center. This Fish Landing Base uses problem-solving to solve existing problems, starting from the formulation stage, location surveys, data collection, literature studies, and comparative studies. To respond these issues, ecological architecture becomes the answer to the problem of design conditions, such as responding according to local conditions both from society and nature. Fish Landing Base in Pantai Cermin expect to respond to users comfortably, creates interaction between users and the environment, and can also form a public space so that it can encourage economic generators based on sources of life in coastal areas, and so become one of the new tourist destinations to enjoy the marine products of Indonesia, especially in Serdang Bedagai, North Sumatera.